PENENTUAN WANPRESTASI PADA PERJANJIAN LISAN YANG TIDAK DITENTUKAN PEMBAGIAN KEUNTUNGAN (STUDI KASUS PUTUSAN PENGADILAN NEGERI TEBO JAMBI NOMOR 18/PDT.G.S/2021/PN.MRT) - Indri Julia Hardini (Jurnal Hukum Adigama, 2021)
Agreements can be made in 2 (two) forms, namely agreements made in writing and agreements made in writing (oral). Oral agreements are often carried out by people in everyday life. However, what if an oral agreement is used in an agreement that causes big losses. near the location of the default in a verbal agreement that does not specify profit sharing?. In researching this problem, the author uses a prescriptive normative method, sourced from primary, secondary, and non-legal data. The results of the study describe the strength of the oral agreement, as well as the evidence and when the state of default occurred in the verbal agreement which did not specify the time for profit sharing.